2021
DOI: 10.3390/s21103485
|View full text |Cite
|
Sign up to set email alerts
|

A Novel V2V Cooperative Collision Warning System Using UWB/DR for Intelligent Vehicles

Abstract: The collision warning system (CWS) plays an essential role in vehicle active safety. However, traditional distance-measuring solutions, e.g., millimeter-wave radars, ultrasonic radars, and lidars, fail to reflect vehicles’ relative attitude and motion trends. In this paper, we proposed a vehicle-to-vehicle (V2V) cooperative collision warning system (CCWS) consisting of an ultra-wideband (UWB) relative positioning/directing module and a dead reckoning (DR) module with wheel-speed sensors. Each vehicle has four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Finally, the time to collision (TTC) is estimated based on the predicted vehicle collision position. The authors of [3] concluded that the proposed method significantly improves the positioning and directing, and the proposed system can efficiently provide collision warning.…”
Section: About the Editorsmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, the time to collision (TTC) is estimated based on the predicted vehicle collision position. The authors of [3] concluded that the proposed method significantly improves the positioning and directing, and the proposed system can efficiently provide collision warning.…”
Section: About the Editorsmentioning
confidence: 98%
“…This Special Issue of Sensors aims at reporting on some of the recent research efforts on this increasingly important topic. The 12 accepted papers in this Issue cover vehicle position estimation [1], vehicle dynamic parameters estimation [2], cooperative collision warning systems [3], small object detection [4], impact identification of the driver's driving performance on executive control function [5], hybrid path planning for autonomous driving [6], trajectory tracking for autonomous driving [7], vehicle stability control [8], vehicle stability and ride comfort control [9], urban platooning protocol design for platoon [10], path planning algorithm for platooning [11], and self-driving architecture design for CAV platoon [12].…”
Section: About the Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Establishing the relative positions of objects is critical for various collaborative applications, including robot movement tracking, virtual/augmented reality (VR/AR), line following, and autonomous vehicles. Establishing the relative positioning between two objects is usually dependent on the deployment of fixed or mobile anchors based on Bluetooth [1], Wi-Fi [2], Global Positioning System (GPS) [3], or ultra-wideband (UWB) radio technology [4]. Most of the solutions applied in relative-position systems use range-measurement techniques.…”
Section: Introductionmentioning
confidence: 99%